Nitrogen accumulation, rather than carbon: nitrogen stoichiometric variation, underlies carbon storage during forest succession. (11th February 2021) - Zou, Junliang; Wu, Juying; Osborne, Bruce; Tobin, Brian; Luo, Yiqi
Abstract: Forest ecosystems play an important role in regulating global temperatures through their capability to take up and store CO2 from the atmosphere, but the magnitude and sustainability of this carbon ( C ) sink is critically dependent on the availability of nutrients, particularly nitrogen ( N ). However, the extent to which the absolute amount of N or modifications in plant and soil C:N ratios controls long-term forest carbon sequestration (Cseq ) remains uncertain. To assess this, we analyzed the results of 135 global field studies that investigated the dynamics of C and N availability during forest succession. The results showed that the accumulation of C and N in plant (including above- and below-ground vegetation) and litter pools decreased with forest age and approached an equilibrium value in the latter stages of stand development. Plant and litter C:N ratios increased during the first 10–20 years and remained relatively stable thereafter. The analysis further showed that the relative importance of a change in the total amount of N or modifications in the C:N ratio, to increases in Cseq, varied with forest age. Whilst the relative importance of a change in the total amount of N increased with forest age, the relative importance of a varied C:N stoichiometry decreased with forest age. Overall, a change in the total amount of N was the more important factor contributing to C storage during forest stand development and the C stored in vegetation dominated the total ecosystem C pool. These results show that ecosystem N availability is a key factor supporting long-term forest Cseq during forest succession. As most of the C is found in above-ground vegetation, this pool is particularly susceptible to abiotic or biotic factors and anthropogenically-related disturbances.